IMMUNOHISTOCHEMICAL STUDY OF ADRENAL GLANDS IN RATS PROGENY GROWN IN THE CONDITIONS OF EXPERIMENTAL HYPO AND HYPERTENSION OF THE MATERNAL BODY - Lutsik, S.A.; Yashchenko, A.M. (World of Medicine and Biology, 2018)
Using immunohistochemical methods — determining cell proliferation and apoptosis markers of KI-67, VEGF and Casp3, respectively — the influence of the experimental hypo- and hyperthyroidism of the maternal organism on the adrenal glands of the offspring (postnatal rats) was studied. Under conditions of the mother’s body hypothyroidismб in the adrenal glands of the offspring on the first postnatal day, a homogeneous distribution of the marker in the adrenocorticocyte cytoplasm in combination with the absence of adrenal medulla rudiments is documented, indicating a certain delay in the organ’s development. On the 10th post-natal day in the adrenal glands of animals in this experimental group, expression of the Ki-67 marker in the cytoplasm and nuclei of adrenocorticocytes in combination with the areactivity of the adrenal medulla cells was detected, indicating the localization of the proliferation processes mainly in the cortical substance. In the adrenal glands of the offspring that developed in the conditions of maternal hyperthyroidism, on the first postnatal day, the absence of cerebrospinal fluid was combined with the weakened expression of the Ki-67 marker in the surface areas of the zona fasciculata and its absence in the adrenal gland cortex zona glomerulosa. In our experiment, the mean weight of fetuses that developed on the background of maternal hyperthyroidism, on the 20th day of prenatal ontogenesis was 5.72 ± 0.24 g (in the control group 2.91 ± 0.14 g), indicating a stimulatory effect of thyroxin on the anabolism processes. On the 1st postnatal day, the weight of newborn rats in the hyperthyroid group (6.19 ± 0.18 g) was approaching the indices of the control group animals (5.84 ± 0.11 g). On the 10th postnatal day, the weight of rats in the experimental conditions was 14.83 ± 0.61 g, whereas in the control group this figure was 17.06 ± 0.15 g, which is evidently due to the predominance of catabolic processes that developed under the influence of maternal hyperthyroidism. The adrenal cells of the offspring that developed under both hypo- and hyperthyroidism conditions of the parent organism were significantly smaller in size, with larger nuclei and elevated nuclear-cytoplasmic ratios compared to the control parameters, indicating the tension in their metabolic processes. The revealed regularities correlate with the results of Vrijkotte et al., which demonstrated the negative influence of both pathological conditions of the maternal body on their offspring development. At the same time, the results of our study suggest that maternal hypothyroidism affects the adrenal glands and other vital organs of the offspring more seriously than hyperthyroidism. The performed study demonstrated significant intensity of both proliferation and apoptosis processes, which accompany postnatal morphogenesis of the adrenal glands; while the most active reorganization is identified in the zona fasciculata of the cortex. On the first day of postnatal development in the background of hypothyroidism, delayed development of adrenal medulla was detected, whereas hyperthyroidism was only accompanied by inhibition of the proliferative activity of cells in the zona glomerulosa. On the 10th postnatal day, an increase in both proliferation and apoptosis in the cortical substance, combined with inhibition of the both processes intensity in adrenal medulla, was documented on the background of the thyroid imbalance.